Qualitative methods for gender research in agricultural development - Rubin, Deborah (International Food Policy Research Institute, 2016)
The rise of mixed methods approaches to development-oriented research has brought new attention to qualitative research methods. This paper describes the use of qualitative approaches to illuminate gender relations in agricultural development research and project implementation. For gender research, qualitative methods can be particularly helpful in illuminating how men and women view their lives. Drawing on literature about social science methods and linking it to recent examples of qualitative methods employed in research and development projects, the paper argues for greater precision in key concepts of gender research, starting with sex and gender. From the many possible qualitative methods used in development work, the paper focuses on several common observational (both direct and participatory) and interview techniques, the latter including key informant and group interviews and focus group discussions. Researchers use various techniques to gather different types of information, for example, mapping techniques to understand men’s and women’s different types of knowledge about their environment and eliciting in-depth information on a single topic with key informants. In a brief discussion of the analysis of qualitative data, the paper notes that informant responses are not “the truth” but need to be assessed against other sources of data. Finally, there is a short discussion of how qualitative data have been used in comparative work. The paper concludes that the results of good qualitative research on gender relations can help identify the locally specific pathways needed to achieve gender-transformative development approaches.